The Influence Of Organization Culture On Employee Performance Mediated By Work Motivation In Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Medan - Hanifa, Nazla; Setiawan, Teguh; Pentana, Sopi (Cattleya Darmaya Fortuna, 2024)
This research aims to determine the influence of organizational culture on work motivation. To determine the partial influence of organizational culture and work motivation on employee performance. To determine the influence of organizational culture on employee performance through work motivation at the Medan City Investment and One Stop Integrated Services Service. The population in this study was 133 people and all of them were used as research samples. The sampling technique used was purposive sampling. The analysis technique used is path analysis. The research results show that organization culture has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, organization culture has a positive and significant effect on work motivation, organization culture has a positive and significant effect on employee performance through work motivation..